The Role of Vascular Endothelial Growth Factor in Metastatic Prostate Cancer to the Skeleton - Emma Roberts; Davina A. F. Cossigny; Gerald M. Y. Quan (Prostate Cancer)
Despite the clinical implication and high incidence of bone and spinal metastases, the molecular mechanisms behind prostate cancer metastasis to bone and spine are not well understood. In this review the molecular mechanisms that may contribute to the highly metastatic phenotype of prostate cancer are discussed. Proangiogenic factors such as vascular endothelial growth factor (VEGF) have been shown to not only aid in the metastatic capabilities of prostate cancer but also encourage the colonization and growth of prostate tumour cells in the skeleton. The importance of VEGF in the complex process of prostate cancer dissemination to the skeleton is discussed, including its role in the development of the bone premetastatic niche, metastatic tumour cell recognition of bone, and bone remodeling. The expression of VEGF has also been shown to be upregulated in prostate cancer and is associated with clinical stage, Gleason score, tumour stage, progression, metastasis, and survival. Due to the multifaceted effect VEGF has on tumour angiogenesis, tumour cell proliferation, and bone destruction, therapies targeting the VEGF pathways have shown promising clinical application and are being investigated in clinical trials.